The Government's Role in the Economy and the Influence of Exports and Imports on North Sumatra's Economic Growth in 2001-2021 - Elisabeth Saida silaban; Hwan Daniel; Noel Tamba; Khairani Alawiyah Matondang; Noni Rozaini (International Journal of Asian Business and Management, 2022)
This study aims to determine the government's role in the economy and the effect of exports and imports on the rate of economic growth in North Sumatra in 2001-2021. This study uses data collection methods and literature studies. Data was collected through the Central Bureau of Statistics for North Uumatera Province and literature studies were carried out by collecting library data, reading and taking notes, and managing research materials. The results of the study show that the government has a role in increasing economic growth and exports and imports in the short term have an influence on the rate of economic growth of 29.69 percent. Export and import variables are not the variables that have the most influence on the rate of economic growth in North Sumatra for the 2001-2021 period. In the short term, there is 70.31% influence from other variables that cannot be explained in this study